On the origin of innovations: The opportunity vacuum as a conceptual model for the explanation of innovation - Patrick Planing (Journal of Innovation and Entrepreneurship, 2017)
The aim of this paper is to transfer the innovation system (IS) approach to the microeconomic level, creating a conceptual framework which helps individual actors to explain, identify, and predict the origin of innovations. Based on the ongoing discussion about the applicability of boundedly rational search and, in particular, the metaphor of an opportunity landscape, the author has developed a conceptual framework for the origin of economic innovations, structured along three dimensions. First, the adjacent possible defines a narrow space of potential first-order combinations of exiting knowledge, which is the trajectory for the new developments in technology and science. Second, the adjacent feasible defines an area of expected cost reduction which enables the exploitation of the new technologies within a threshold. Finally, the adjacent acceptable represents a small area on the current edges of socially accepted behavior, which currently only innovators embrace, but soon will reach the early majority of adopters. It is, however, the moment when all three dimensions achieve an intersecting area, when the opportunity vacuum (OV) is created. The OV is a space, which strongly attracts innovation and often creates multiple inventions at the same time emerging independently. While this model is aimed at explaining the origin of economic innovations in retrospective, it can also be applied as a framing method to anticipate future economic novelty.
Keywords: 650; Innovation; Origins; Opportunity mapping; Adjacent possible; Entrepreneurship